Capitalizing on a "Huge Resource": Successful Aging and Physically Active Leisure Perspectives from Older Males. (4th July 2022) - Deneau, Jordan; van Wyk, Paula M.; Horton, Sean
Abstract: A major concern in the context of aging populations is improving patterns of active leisure involvement. However, there is insufficient knowledge pertaining to the relationship between successful aging and active leisure. Preliminary evidence indicates older Canadian women have varying beliefs about the ways they can age successfully and the role physical activity may have in this process. To more fully inform health promotion initiatives, the current study explored the related perspectives of 19 older Canadian men (75–90 years of age) who varied in their level of physical activity involvement. Data were collected through semi-structured interviews and analyzed through the use of standard coding and comparison procedures. Overall, older men appeared to also use multiple perspectives to frame the intersection of successful aging and physically active leisure. Researchers, practitioners, and policy makers should be aware of these nuances so that aging-related programs and policies may be tailored accordingly.